Fluorophlogopite-bearing and carbonate metamorphosed xenoliths from the Campanian Ignimbrite (Fiano, southern Italy): crystal chemical, geochemical and volcanological insights. (1st October 2017) - Lacalamita, M.; Balassone, G.; Schingaro, E.; Mesto, E.; Mormone, A.; Piochi, M.; Ventruti, G.; Joachimski, M.
Fluorine-, boron- and magnesium-rich metamorphosed xenoliths occur in the Campanian Ignimbrite deposits at Fiano (southern Italy), at ∼50 km northeast of the sourced volcanic area. These rocks originated from Mesozoic limestones of the Campanian Apennines, embedded in a fluid flow. The Fiano xenoliths studied consist of ten fluorophlogopite-bearing calc-silicate rocks and five carbonate xenoliths, characterized by combining mineralogical analyses with whole-rock and stable isotope data. The micaceous xenoliths are composed of abundant idiomorphic fluorophlogopite, widespread fluorite, F-rich chondrodite, fluoborite, diopside, Fe(Mg)-oxides, calcite, humite, K-bearing fluoro-richterite and grossular. Of the five mica-free xenoliths, two are calcite marbles, containing subordinate fluorite and hematite, and three are weakly metamorphosed carbonates, composed only of calcite. The crystal structure and composition of fluorophlogopite approach that of the end-member. The Fiano xenoliths are enriched in trace elements with respect to the primary limestones. Comparisons between the rare-earth element (REE) patterns of the Fiano xenoliths and those of both Campanian Ignimbrite and Somma-Vesuvius marble and carbonate xenoliths show that the Fiano pattern overlaps that of Somma-Vesuvius marble and carbonate xenoliths, and reproduces the trend of Campanian Ignimbrite rocks. Values of δ13C and δ18O depict the same trend of depletion in the heavy isotopes observed in the Somma-Vesuvius nodules, and is related to thermometamorphism. Trace-element distribution, paragenesis, stable isotope geochemistry and data modelling point to infiltration of steam enriched in F, B, Mg and As into carbonate rocks at a temperature of ∼300–450°C during the emplacement of the Campanian Ignimbrite.